Invasi Militer Rusia ke Ukraina pada Tahun 2022: Tujuan, Alasan, dan Implikasi - Firdaus, Muhammad Fadhil; Argenti, Gili; Gustianti, Nurbani Adine (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the objectives, reasons, and implications of the Russian military invasion of Ukraine that began on February 24, 2022. This invasion is one of the important events in global geopolitics that affects international stability, European security, and international law, especially regarding violations of human rights and humanitarian law. This study uses a qualitative approach with a literature study, relying on secondary sources such as books, journal articles, international reports, and official documents relevant to this conflict. This analysis identifies several reasons that drove Russia to carry out the invasion, including strategic interests in maintaining influence in the Eastern European region, concerns about NATO expansion, and the desire to strengthen political dominance in the region. This study also examines the implications of the invasion on Ukraine, which include major losses in terms of casualties, destruction of infrastructure, and impacts on the Ukrainian economy and society. In addition, this invasion also had a broad impact on international relations, worsening Russia's relations with Western countries, and triggering significant economic sanctions against Russia. Through this analysis, this study seeks to provide a deeper understanding of the factors underlying the Russian invasion and its impact on global geopolitical stability and the future of international law in dealing with armed conflict.